Curriculum Development at the BUNAYYA Al-Qur’an Guidance Institution Based on Islamic Education Management - Syamkhotsaa, Wellaa; Priyanggani, Wulan; Ain, Dhea Savana Qurrota (QUALITY, 2026)
This study describes the implementation of Islamic Education Management (IEM) in the curriculum development process at the BUNAYYA Qur’an Guidance Centre.The goal is to improve the quality of Qur’anic learning and foster Islamic character in students. The study employs a qualitative descriptive approach with curriculum development at the BUNAYYA Qur’an Guidance Centre as the subject of the research. Data were collected through interviews, observations, and documentation involving the center’s management, teachers, and parents. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. Data validity was tested through triangulation of sources and methods. The research findings indicate that the BUNAYYA Institute has fully implemented the MPI functions in its curriculum development. During the planning stage, the curriculum was formulated through consultation between management, teachers, and parents to integrate the needs of Qur’anic learning and Islamic values. The organization stage is carried out through a clear division of tasks based on the principles of trust and brotherhood. The implementation of the curriculum emphasizes active learning, recitation, memorization, and internalization of Qur’anic etiquettevalues. Monitoring is conducted through periodic evaluations of students’ reading skills, memorization, and behavior. These findings suggest that applying the principles of consultation, trustworthiness, justice, and kindness in curriculum development can enhance the quality of Qur’anic learning and strengthen the formation of students’ Islamic character.